(untitled) (Baghdad Science Journal, 2016)
The polymers modified Poly(vinyl chloride) differ in their tendency to photo oxidation comparing with that unmodified. It has been studied Photostability for modified Poly(vinyl chloride) chains using Schiff’s bases derivative of (5-amino-1, 3, 4-thiadiazole-2-thiol) in a manner casting of plastic chips with thickness (40) in a solvent Tetrahydrofuran. It has been determined the effectiveness Photostability of these modified polymers through the photo degradation rate constant for photostabilizer (kd) for the modified Poly (vinyl chloride). Attributed efficiency of these Poly(vinyl chloride) chips in Photostability by replace the atom Cl Poly(vinyl chloride) chains ends more stable than light stabilizer.